Avaliação antimicrobiana e dos parâmetros salivares de dentifrícios contendo óleos essenciais: estudo duplo-cego, randomizado - Marinho, Rebeca Bastos Vasconcelos (2019)
The present work aimed to assess the antibacterial efficacy, effect on salivary parameters and side effects of dentifrices containing different concentrations of essential oils in association with sodium fluoride for future testing in a prospective study in pediatric patients. Sixty healthy adults, both sexes, aged 18-45 years, without active caries lesions joined the study. Subjects were randomly assigned to brush their teeth during one minute with one of 5 dentifrices: 1%Lippia sidoides Cham (LSO), 2%LSO, 1% Carvacrol + Timol (Car+Thy), 0,5%Car+Thy or 1000 ppm de fluoreto de sódio (Control). All dentifrices contained 1000ppm of fluoride. Saliva was collected before (I) and after (F) toothbrushing to measure flow rate, pH, buffer capacity and mutans streptoccocci (MS) levels in saliva. A questionnaire (SQ) was applied to evaluate patient satisfaction and side effects. A significant difference was observed between I and F flow-rates: 1%LSO (p=0.002), 2%LSO (p=0.045); pH: Control (p=0.013), 1%LSO (p=0.006), 2%LSO (p=0.004), 0,5%Car+Thy (p=0.013); and buffer capacity - 1%LSO (p=0.015); 1%Car+Thy (p=0.019). MS reduction after toothbrushing was only observed with 2%LSO (p= 0.013) e 1%Car+Thy (p=0.021). SQ demonstrated burning sensation as the most evident side-effect noted by patients, followed by odor perception and sense of cleanliness. Burning sensation showed significant differences between 1%LSO and 1%Car+Thy (p=0.008); 2%LSO and 1%Car+Thy (p=0.003). Our results suggest that dentifrices containing LSO, Car and/or Thy in association with fluoride promote an increase in salivary flow rate, pH and buffer capacity, generating a reduction in MS at higher concentrations. In spite of a greater burning sensation, 2%LSO and 1%Car+Thy showed the best outcome for future testing.